Reversible gating of singlet fission by tuning the role of a charge-transfer state - Yifan Bo; Yuxuan Hou; Dominic A. X. Lavergne; Timothy Clark; Michael J. Ferguson; Rik R. Tykwinski; Dirk M. Guldi (Nature Communications)
Abstract Stimulus-responsive triplet excited states and multiexcitonic logic gates have garnered increasing interest. Singlet fission is an efficient multiple exciton generation process, in which one singlet converts into two triplets. Singlet fission is, however, rarely reported to be switchable by external stimuli. Here we design a meta-diethynylphenylene-linked tetracene dimer featuring pyridyl endgroups that function as an acid/base-responsive switch, enabling the reversible modulation of singlet fission. In its neutral form, the interchromophore charge-transfer state facilitates singlet fission and promotes the formation of a correlated triplet-pair state. Upon treatment with acid, protonation of the pyridyl nitrogens generates a more strongly electron-accepting pyridinium, leading to an intra-chromophore charge-transfer state, which inhibits singlet fission. Finally, an IMPLICATION logic gate is constructed by using acid and base as inputs and monitoring the formation of triplet excited states based on singlet fission.